The Old Testament outside the realm of the Church : a case from Madagascar - Razafindrakoto, Georges (Old Testament essays, 2006)
The article describes and discusses some cases of Old Testament interpretation in the context of Malagasy traditional religion. It is claimed that the Bible - and not least the Old Testament - is regarded as a common heritage for Christians as well as traditionalists in Madagascar. After a survey of various examples of how the Old Testament is being interpreted in traditional religious contexts, it is argued that the use of the Old Testament aims at legitimizing traditional religion vis-à -vis Christianity.